Die Akten des Kaiserlichen Reichshofrats (RHR) - Serie II Antiqua Band 2: Karton 44-135 : - Sellert, Wolfgang (2019)
This is a new listing of the previously untapped judicial files of the Aulic Council kept in the Austrian State Archives. With the series "Alte Prager Akten", "Antiqua" and "Denegata antiqua", the long-term project will make accessible almost one third of the approximately 80,000 files. The index provides information on the parties as well as new findings on conflicts from the history of law and constitution, social and economic history, criminal, military, technical and craft history. It also records reports addressed to the Emperor by important officials of the Empire and various requests for support of subjects in distress.